TI_GERICHTE 50.2008.5 vom 7. November 2011 , Espropriazione formale di uno scorporo di terreno. Metodi di stima del valore venale - TI Tribunale d'appello (2011)
Espropriazione formale di uno scorporo di terreno. Metodi di stima del valore venale